Flow pattern analysis for oscillatory flow inside resonator tube for thermoacoustic refrigerator using PIV measurement - Siti Norsyahira, Mohd Zahari; Nor Atiqah, Zolpakar; Nurrizatul Atikha, Rahmat (ISRES Publishing, 2022)
A thermoacoustic refrigerator system is an alternative cooling system that uses air or inert gas as a cooling fluid. The environmentally friendly characteristics make this system potential as a green alternative for a cooling system. However, due to its low efficiency compared to conventional vapor compression systems, its application is limited. Since a thermoacoustic refrigerator is based on the oscillatory flow to generate a cooling effect, the understanding of a flow pattern inside the resonator tube is crucial to enhance the coefficient of performance (COP) of the system. In this study, Particle Image Velocimetry (PIV) is used to visualize the flow pattern inside the resonator tube. PIV is an optical, noninvasive technique that uses a high-speed camera, highpower multipulse laser, and synchronizer to capture the particle movement in the resonator with a length of 1 m, and the frequency applied is 100 Hz. The result shows that there is a formation of a vortex at the entrance and at the exit of the stack. The formation of the vortex at the entrance induces by the flow disturbance created by the stack. This vortex formation varied with the location of the stack and the amplitude of the wave applied. The velocity distribution of the particle inside the resonator tube is also presented and discussed in this paper. These findings indicate that the flow patterns and velocity distribution should be further analyzed to interpret the effect of these characteristics on the system. These results are expected to give a better understanding of the future development of the thermoacoustic system.